Regulated expression of human beta-defensin-2 leads to altered phenotype and growth patterns of cultured human embryonal kidney cells - Zhuravel, E.; Lytvyn, D.; Soldatkina, M.; Zeleniy, S.; Shestakova, T.; Pogrebnoy, P. (Experimental Oncology, 2006)
Aim: To create cell line with regulated expression of human beta-defensin-2 (hBD-2) and evaluate the influence of expressed peptide on its phenotypic and growth patterns. Materials and Methods: Using cloning techniques, on the base of human embryonic kidney cells of HEK293T line, stable T-rex HEK-hBD2-m cell subline expressing mature biologically active hBD-2 molecule upon the presence of tetracycline in culture medium was generated. The morphological patterns, growth characteristics and colony forming activity of these cells were studied using routine techniques. Results: T-rex HEK-HBD2-m cell subline was shown to express both mRNA and hBD-2m protein upon the presence of 1 µg/ml tetracycline in culture medium as it was demonstrated by RT-PCR and immunocytochemical approach. Upon prolonged expression of hBD-2, the cells acquired special features: they lost ability to grow in monolayer in vitro and to form colonies in soft agar, characteristic to parental HEK293T cells, but possess higher growth rate and longer survival in FBS-free medium than wild type cells. Conclusion: Expression of hBD-2 in T-rex HEK-HBD2-m cell subline results in specific biological consequences that favor cell survival.